Suppression of Slit3 induces tumor proliferation and chemoresistance in hepatocellular carcinoma through activation of GSK3β/β-catenin pathway - Lui Ng; Ariel K. M. Chow; Johnny H. W. Man; Thomas C. C. Yau; Timothy M. H. Wan; Deepak N. Iyer; Virginia H. T. Kwan; Ronnie T. P. Poon; Roberta W. C. Pang; Wai-Lun Law (BMC Cancer, 2018)
Abstract Background It is essential to understand the mechanisms responsible for hepatocellular carcinoma (HCC) progression and chemoresistance in order to identify prognostic biomarkers as well as potential therapeutic avenues. Recent findings have shown that SLIT3 appears to function as a novel tumor suppressor gene in various types of cancers, yet its clinical correlation and role in HCC has not been understood clearly. Methods We determined the transcript levels of Slit3 in tumor and adjacent normal tissues within two cohorts (N = 40 and 25) of HCC patients, and correlated the gene expression with the clinicopathological data. Subsequently, the functional effects and underlying molecular mechanisms of Slit3 overexpression and/or repression were studied using cell-line and mouse models. Results Our results demonstrated a repression in Slit3 expression in nearly 50% of the HCC patients, while the overall expression of Slit3 inversely correlated with the size of the tumor in both cohorts of patients. Stable down-regulation of Slit3 in HCC cell-lines induced cell proliferation in vitro and tumor growth in vivo, while stable Slit3 overexpression repressed these effects. Molecular investigations showed that the stable Slit3 repression-induced cell proliferation was associated with a higher expression of β-catenin and a repressed GSK3β activity. Moreover, Slit3-repression induced chemoresistance to sorafenib, oxaliplatin and 5-FU through impairment of β-catenin degradation and induction of cyclin D3 and survivin levels. The effects induced by stable Slit3-repression were diminished by transient repression of β-catenin by siRNA approach. Conclusion This study suggests that Slit3 acts as a tumor suppressor in HCC by repressing the tumor growth and thus tumor progression. Low Slit3 level indicates a poor response of HCC cells to chemotherapy. Restoration or overexpression of Slit3 is a potential therapeutic approach to repress the tumor growth and enhance the efficacy of chemotherapeutic agents.